Medieval Art, National Architectural Heritage and Museums in Late 19th Century Romania - Cosmin Minea (Anastasis: Research in Medieval Culture and Art, 2021)
This article describes how the material heritage was given new shape and meaning in the context of the new nation-state of Romania. It starts by looking at the history of the first public museum in Romania, namely the Museum of Natural History and Antiquities in Bucharest and also at the broader interest in the Roman antiquities in 19th century Romania. It then focuses on the first restoration of historical monuments and the initiatives of two of the most well-known architects at the time to establish museums of religious art: André Lecomte du Noüy (1844-1914) and Ion Mincu (1852-1912). The process of creating a national heritage for Romania has led to the design of valuable new buildings and was underpinned by a powerful will to modernise the country. At the same time, it has represented a destructive force. The built fabric of historical sites and historical artefacts were reshaped, rebuilt, given new meanings and context, so that to fit into the political objectives of the new nation-state. The article will balance and analyse the significance of these various efforts to restore historical monuments and establish the first museums of Romanian heritage.